An improved method for selection of wheat genotypes for tolerance to crown rot caused by Fusarium pseudograminearum. Issue 6 (18th April 2021) - Kelly, Alison; Macdonald, Bethany; Percy, Cassandra; Davies, Philip
Abstract: Achieving genetic gain when selecting for genotypes with favourable grain production traits in the presence of the fungal pathogen Fusarium pseudograminearum can involve potentially competitive objectives of breeding for tolerance and breeding for resistance. A method for the selection of genotypes for both tolerance and resistance to crown rot in wheat, caused by this fungal pathogen, is presented through a combined analysis of grain yield and symptoms of disease severity across inoculated and uninoculated treatments. The symptoms of disease severity are measured as basal stem browning in the plant, and this trait provides a measure of resistance in this study. The measurement of grain yield in uninoculated and inoculated treatments provides a measure of yield potential and yield in the presence of disease, respectively. Interpretation of analysis results through the regression inherent in the statistical model allows us to derive and select for three traits of interest. Firstly, yield retention can be derived from a random regression of yield of genotypes in inoculated versus uninoculated treatments, independently of yield potential in that environment. Secondly, severity of disease symptoms in inoculated treatments can be used to select genotypes with superior resistance. Finally, a tolerance measure can be derived from the yield retention, when it is assessed independently of the disease severity measured as stem browning. In theory, this method is superior to traditional approaches of forming a yield difference or a percentage yield loss calculation. In practice, genetic gain can be made for tolerance through accurate phenotyping of the trait, independently of resistance in that environment.